Happiness perspective of migrant labor households in the northeast, Thailand - Ayuwat, Dusadee; Narongchai, Wanichcha; Rengmanawong, Adirek; Auraiampai, Nattawat (International Journal of Engineering and Technology, 2018)
This research focused on happiness perspectives of the migrant labour households in the Northeast, Thailand. The study relied on the qualitative methodology. The in-depth interview was conducted with key informants: village headman, senior persons, local officers and twelve heads of the international migrant households who had variation of migration patterns, selected by snowball techniques in one village within the O-lo District, Chaiyaphum Province. Data collection was done during April to May, 2017. The results were descriptive content analysis technique. The results indicated that most of the migrant labour households were farmers, grew rice and sugarcane and produced handicraft. Male labourers were the main group of the international migrants. The migrant labour households had only one labourer working abroad, with 2-month to10-year period of migration. The migration method that the labourers used in many destinations were through companies, brokers, the Department of Employment, or themselves. The migrant labour households defined happiness as good relationship within households, financial security, ability to manage debt and tension, household members being in good health, good relationship with others households, and safe and convenient life. The method of finding jobs abroad was related to working security of migrant labourers and happiness of the migrant labour households.Â